2010
DOI: 10.5194/nhess-10-1171-2010
|View full text |Cite
|
Sign up to set email alerts
|

Operational flood management under large-scale extreme conditions, using the example of the Middle Elbe

Abstract: Abstract. In addition to precautionary or technical flood protection measures, short-term strategies of the operational management, i.e. the initiation and co-ordination of preventive measures during and/or before a flood event are crucially for the reduction of the flood damages. This applies especially for extreme flood events. These events are rare, but may cause a protection measure to be overtopped or even to fail and be destroyed. In such extreme cases, reliable decisions must be made and emergency measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…For this IC, a large-scale and taskspecific stochastic-conceptual precipitation-runoff (SCPR) model was developed. Distributed daily input of the IC was derived by interpolation of observed precipitation depths (inverse-distance Kron et al, 2010) shows the reach of the Middle Elbe river which was chosen as case study area of the joint research project to which the work of present paper contributed. method) and temperatures (modified nearest-neighbour method with altitude gradients) to a 5 × 5 km grid.…”
Section: Hydrological Simulation In the German Basin Partmentioning
confidence: 99%
See 2 more Smart Citations
“…For this IC, a large-scale and taskspecific stochastic-conceptual precipitation-runoff (SCPR) model was developed. Distributed daily input of the IC was derived by interpolation of observed precipitation depths (inverse-distance Kron et al, 2010) shows the reach of the Middle Elbe river which was chosen as case study area of the joint research project to which the work of present paper contributed. method) and temperatures (modified nearest-neighbour method with altitude gradients) to a 5 × 5 km grid.…”
Section: Hydrological Simulation In the German Basin Partmentioning
confidence: 99%
“…These hydrological simulations contributed to the joint research project "Operational flood management under large-scale extreme conditions, using the example of the Middle Elbe" (funded by the German Ministry of Education and Research) with further sub-projects on meteorological, hydraulic and geotechnical (dike monitoring) issues. A summary of advancements and coupling of tools as well as interdisciplinary derivation and evaluation of extreme flood scenarios performed in this joint research project can be found in Kron et al (2010). Present paper emphasises the largescale hydrological simulation technique newly developed for the German part of the Elbe basin (see Sect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These infrastructure components are often widely distributed within coastal cities (Hung et al, 2009) and connected spatially through waterways, creating a complex topology of networked systems (Barrat et al, 2004). As the real-time operation of flood control systems is crucial for mitigating the damaging impacts of floods (Shim et al, 2002), the inability to understand this network complexity may result in imprecise operational decisions leading to the failure of the hydrological infrastructure system during flood events (Akmalah and Grigg, 2011;Kron et al, 2010;Kundzewicz, 1999). This situation presents a significant problem in coastal mega-cities in which the consequent failure of the hydrological network exacerbates flood hazards, causing significant loss of life and damage to property worth billions of dollars (Brinkman and Hartman, 2008;Few, 2003;Ward et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Imprecise operational decision making during flood events may also lead to the failure of the hydrological network (Akmalah and Grigg, 2011;Kron et al, 2010), which in turn may result to a breakdown in other important infrastructure systems such as energy, transportation, and communication networks (Caljouw et al, 2005;Chen et al, 2005). Therefore, in designing a solution to improve real-time operational decision making in flood control systems, the capability to understand the interdependencies between hydrological networks and other critical infrastructure is crucial.…”
Section: Introductionmentioning
confidence: 99%